Implementation of TPA (Third Party Access) principle in Polish energy sector - Lech, Aleksandra (Comparative Economic Research. Central and Eastern Europe, 2010)
The liberalization of energy sector in Poland is conducted according to the conclusions deriving from the criticism of the traditional theory of regulation – the TPA principle is an instrument enabling introducing competition in energy trade subsector. However, in spite of formal assurance that the right to change electricity supplier is granted to all recipients, only a small number of entitled entities exercise this privilege. It is only the group of big industrial buyers among whom growing interest to exercise the TPA principle can be observed. The barriers to changing electricity supplier include economic, technical and formal ones. Removing them in the future will result in the increase of competition scale in energy sector.